Optimization of batch bioreactor conditions for production of fermented spirulina by mixed culture of Lactobacillus helveticus and Kluyveromyces marxianus and effect of bioreactor conditions on some bioactive properties - Yay, Cansu (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2023)
The aim of this study was to find the optimal batch conditions at the bioreactor level for the growth of a mixed culture of Lactobacillus helveticus B-4526 and Kluyveromyces marxianus Y329 to diversify and/or improve the bioactive properties (antioxidant activity, antimicrobial activity, ACE inhibitory activity, total phenolic content) of Spirulina platensis biomass and to investigate the effect of ultrafiltration and in vitro digestion on the promising fermented Spirulina (FS) product. The operating conditions studied were aeration rate (0.5 vvm FS and 1 vvm FS), dissolved oxygen level (cascade FS) and pH (controlled pH FS). It was observed that all bioreactor conditions supported the growth of microorganisms. The FAA content was higher in all production conditions compared to unFS. The essential amino acid content also increased in all fermentations, with the cascade FS having the highest essential amino acid content. Although FS products did not show antimicrobial activity, they have enhanced bioactivities in terms of other activities (TEAC, ACE-I, TPC), and cascade FS has the most remarkable bioactive properties. Cascade FS also had different groups of VOCs. Sensory analysis revealed that FS products had less "seaweed", "muddy/earthy" and "grass" flavors compared to unFS. Changes in bioactivities during in vitro digestion showed that FS had largely conserved its activity at the end of gastrointestinal digestion compared to unFS. FS fractions of 5-10 kDa and <5 kDa were effective in DPPH scavenging activity and TEAC, respectively. Overall, this study demonstrated the importance of optimizing bioreactor conditions to improve the properties of Spirulina.

Bu çalışmanın amacı, Spirulina platensis biyokütlesinin biyoaktif özelliklerini (antioksidan aktivite, antimikrobiyal aktivite, ACE inhibitör aktivitesi, toplam fenolik içerik) çeşitlendirmek ve/veya geliştirmek için Lactobacillus helveticus B-4526 ve Kluyveromyces marxianus Y329 karışık kültürünün büyümesi için biyoreaktör seviyesinde optimum kesikli çalışma koşullarını bulmak ve ultrafiltrasyon ve in vitro sindirimin umut verici fermente Spirulina (FS) ürünü üzerindeki etkisini araştırmaktır. İncelenen koşullar havalandırma hızı (0,5 vvm FS ve 1 vvm FS), çözünmüş oksijen seviyesi (kaskat FS) ve pH (kontrollü pH FS) olmuştur. Tüm biyoreaktör koşullarının mikroorganizmaların büyümesini desteklediği gözlemlenmiştir. FAA içeriği tüm üretim koşullarında unFS'ye kıyasla daha yüksektir. Esansiyel amino asit içeriği de tüm fermantasyonlarda artmış ve kaskat FS en yüksek esansiyel amino asit içeriğine sahip olmuştur. FS ürünler herhangi bir antimikrobiyal aktivite göstermemesine rağmen diğer aktiviteler bakımından gelişmiş biyoaktivitelere (TEAC, ACE-I, TPC) sahiptir ve kaskat FS en dikkat çekici biyoaktif özelliklere sahiptir. Kaskat FS ayrıca farklı VOC gruplarına sahiptir. Duyusal analiz, FS ürünlerinin unFS'ye kıyasla daha az "deniz yosunu" çamurlu/topraklı" ve "çimen" tatlarına sahip olduğunu ortaya koymuştur. In vitro sindirim sırasında biyoaktivitelerdeki değişiklikler, FS'nin gastrointestinal sindirimin sonunda unFS'ye kıyasla aktivitesini büyük ölçüde koruduğunu göstermiştir. FS 5-10 kDa ve <5 kDa fraksiyonları sırasıyla DPPH süpürme aktivitesinde ve TEAC'da etkili olmuştur. Genel olarak, bu çalışma Spirulina'nın özelliklerini iyileştirmek için biyoreaktör koşullarının optimizasyonunun önemini göstermiştir.
Lactobacillus helveticus ve Kluyveromyces marxianus karışık kültürü ile fermente spirulina üretimi için kesikli biyoreaktör koşullarının optimizasyonu ve biyoreaktör koşullarının bazı biyoaktif özellikler üzerine etkisi
Keywords: Biyoteknoloji; Biotechnology